INTRODUCING LOCAL WISDOM THROUGH NARRATIVE: TEACHING ENGLISH IN HIGHER EDUCATION - Titis Sulistyowati; Sri W Surachmi (Indonesian EFL Journal, 2020)
It is very important to introduce and continue the local narrative and their values to the next generation. This paper is part of a larger research on narrative writing for higher education level students organized in a genre writing class. In this paper, the writers focus on exploring the students’ understanding of moral values in the local narratives constructed during genre writing activities. This paper also describes the teacher’s feedback on the students’ writing quality. This study involved 20 students from the English Education Department of Muria Kudus University. Guided questions were used in the interview session to explore the students’ understanding of the local narratives and moral values. The review of students’ papers was used to analyze the teacher’s feedback to explore the students’ quality of writing. Keywords: local wisdom; narrative; character building; writing.